Fuzzy Logic Based Decision System for the Local Control of Signalized Intersections - Ravago, Reuben J. (Philippine Engineering Journal; Vol 17 No 1 (1996), 2021)
The objective of this study is to develop a fuzzy logic based system which will effectively control a 4-lane intersection, The controller is based on fuzzy logic and it has two inference engines which determine the actions in the intersection. One fuzzy logic engine decides the phase length for a direction pair while the other decides the phase splits. The system is adaptive in that it makes decisions based on currently available traffic data. Testing of the system against a conventional traffic simulation have shown very favorable results.